EMPAT SRIKANDI KULINER BALI: PERAN PEREMPUAN DALAM PEMBANGUNAN PARIWISATA BERKELANJUTAN1 - Darma Putra, I Nyoman (JURNAL MASTER PARIWISATA; Volume 01, Nomor 01, Juli 2014DO - 10.24843/JUMPA.2014.v01.i01.p04)
This article discusses the role of women in supporting sustainable tourism development in Bali by promoting Balinese cuisine to the tourism world. To date, studies on the role of Balinese women in the tourism industry have looked mainly at women as ordinary workers or professionals. In fact, Balinese women operate as culinary entrepreneurs who have not only been successful in introducing Balinese cuisine to the world of tourism but have opened up job opportunities for men and women alike. The data presented in this article was collected through observation of four leading Balinese women who run successful local culinary outlets or restaurants offering local dishes, and is complemented by interviews and other published sources relating to their business activities. The four pioneering women surveyed are Men Tempeh of Gilimanuk (West Bali) serving chicken betutu, the suckling pig restaurant manager Ibu Oka in Ubud, the owner of Made’s Warung Ni Made Masih, and the catering company owner Ibu Warti Buleleng, based in Denpasar. This article concludes that these four Balinese culinary heroines or srikandi have successfully managed to preserve and promote Balinese dishes to the world of tourism while contributing to the sustainable development of Balinese tourism by providing opportunities for tourists to experience local cuisine.